H2O-controlled selective thiocyanation and alkenylation of ketene dithioacetals under electrochemical oxidation. Issue 13 (3rd June 2019) - Wen, Jiangwei; Zhang, Longfei; Yang, Xiaoting; Niu, Cong; Wang, Shuangfeng; Wei, Wei; Sun, Xuejun; Yang, Jianjing; Wang, Hua
Abstract : Efficient and H2 O-controlled selective thiocyanation and alkenylation of internal olefins, to afford tetrasubstituted olefins under electrochemical oxidation, has been successfully developed. Abstract : Efficient and H2 O-controlled selective thiocyanation and alkenylation of internal olefins, to afford tetrasubstituted olefins under electrochemical oxidation, has been successfully developed. This transformation can present a critical feature wherein neither exogenous oxidants nor catalysts are required. Notably, such an electrochemical oxidation-based synthetic strategy exhibits excellent tolerance towards functional groups and can be easily scaled up with good efficiency.